2014
DOI: 10.1007/s12012-014-9246-2
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Dysfunction with Increased Vascular Leakage Response in Mice Systemically Exposed to Arsenic

Abstract: The mechanisms underlying cardiovascular disease induced by arsenic exposure are not completely understood. The objectives of this study were to investigate whether arsenic-fed mice have an increased vascular leakage response to vasoactive agents and whether enhanced type-2 protein phosphatase (PP2A) activity is involved in mustard oil-induced leakage. ICR mice were fed water or sodium arsenite (20 mg/kg) for 4 or 8 weeks. The leakage response to vasoactive agents was quantified using the Evans blue (EB) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Our data also showed that systemic arsenic exposure markedly decreased aortic SMC area in absence of aortic luminal fatty streaks, accompanied by a significantly decreased SM22 level in wild-type ICR mice on a regular diet. Recent studies indicate the presence of microvascular dysfunction with increased vascular leakage in response to inflammatory stimuli in mice systemically exposed to arsenic [18,19]. Thus, our data showed arsenic-mediated alterations of vascular structure in wild-type mice, suggesting an impact of arsenic on vascular structure independent of plasma hyperlipidemia.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our data also showed that systemic arsenic exposure markedly decreased aortic SMC area in absence of aortic luminal fatty streaks, accompanied by a significantly decreased SM22 level in wild-type ICR mice on a regular diet. Recent studies indicate the presence of microvascular dysfunction with increased vascular leakage in response to inflammatory stimuli in mice systemically exposed to arsenic [18,19]. Thus, our data showed arsenic-mediated alterations of vascular structure in wild-type mice, suggesting an impact of arsenic on vascular structure independent of plasma hyperlipidemia.…”
Section: Discussionsupporting
confidence: 65%
“…A previous study suggested that arsenicinduced endothelial dysfunction occurs through oxidative stress events that lead to atherosclerosis in animal models [17]. Recent studies indicate that microvascular dysfunction and increased vascular leakage occur in response to inflammatory stimuli following systemic arsenic exposure, even in wild-type mice [18,19]. In the present study, we examined whether systemic arsenic exposure induced morphological and biochemical alterations of SMCs in the aorta of ICR mice.…”
Section: Introductionmentioning
confidence: 87%
“…Chronic exposure to 200 or 1000 ppb iAs in drinking water also showed development of atherosclerotic plaques in the macrovasculature of ApoE-/- mice [20] . Mice administered 20 mg/kg of sodium arsenite in water showed increased vascular leakage [5] . At a similar dose, iAs had anti-angiogenic activity in solid tumor models by decreasing expression of vascular endothelial growth factor (VEGF) [34] .…”
Section: Introductionmentioning
confidence: 97%
“…Animal studies have produced conflicting results [5] , [6] , [28] . In FVB female mice, chronic exposure to 100 ppb iAs III in drinking water for 22 weeks was shown to induce hypertension and cardiac hypertrophy [25] .…”
Section: Introductionmentioning
confidence: 99%
“…Because ~140 million people worldwide are at risk of exposure to excessive levels of naturally occurring As in well water and groundwater [ 1 ], exposure of As in drinking water is a serious public health problem. Several studies have shown that chronic exposure to As is associated with increased incidence of several human diseases including cardiovascular disease [ 2 ]. Although the molecular mechanism in which As causes vascular disease has not yet been defined, it is well accepted that increased toxicity of vessels cells resulting from As-induced reactive oxygen species (ROS) is significant.…”
Section: Introductionmentioning
confidence: 99%